Clinicoetiological and imaging profile of intracerebral haemorrhage in a tertiary care hospital of Western Odisha - Karua, Purna Chandra; Joy, Shiny (International Journal of Research in Medical Sciences, 2020)
Background: Intracerebral hemorrhage has an annual incidence of 10-30/100,000 population, accounting for 2 million (10-15%) of about 15 million strokes worldwide each year. The outcome of ICH depends on the clinical presentation and radiological parameters. The objective of current study was to study the etiology, clinical patterns and imaging profile in patients of intracerebral hemorrhage. Methods: All patients admitted in department of medicine, VIMSAR, Burla, with a diagnosis of ICH during a period of November 2017 to October 2019 were evaluated for their clinical presentation, etiology and radiological parameters. Results: A total of 105 patients with a diagnosis of ICH were included in the study. The sites of ICH were basal ganglia (49%) followed by lobar (19%), thalamus (14%), cerebellum (11%) and brain stem (8%). A pre-diagnosis of hypertension was present in 33% of the cases. Headache was the most common presenting symptom, present in 38.2% of patients followed by paralysis in 29.5%, vomiting in 27.6% and seizures in 20.9% of cases. Overall mortality rate was 39%. The mean GCS of patients who expired was 8.8 when compared to 11.28 of those patients who survived (p=0.00009). The mean hematoma size of patients who expired was 20.98 while that of those who survived was 17.41 (p=0.047). The presence of IVC was associated with mortality (p=0.006). Conclusions: A lower GCS at presentation and a mean hematoma volume >20 ml with intraventricular extension at presentation are associated with increased mortality in ICH.